Harmonisation of Regulations About A Reasonable Agreement and Actions to Achieve Sustainable Development Alignment of Goals - Ria Karlina Lubis (Universitas Sumatera Utara, 2023)
The achievement of basic rights related to adequate housing is one of the goals of Indonesia's full commitment to realizing sustainable development. This study aims to harmonize regulations regarding reasonable agreements and actions to achieve fitness for sustainable development goals. This study will concentrate on examining the harmonization of the actual contents of regulations by using a concept approach and legal methods, taking into account the importance of relevant laws to support these development goals. Defining what constitutes a viable and sustainable organization is the first step in the discussion. The next section provides an overview of how the definition of